2009
DOI: 10.1177/003172170909000709
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Professional Development?

Abstract: hat do we really know about the relationship between professional development and improvements in student learning? What evidence validates that relationship, and how trustworthy is that evidence? What does that evidence tell us about the characteristics of truly effective professional development activities? These questions guided one of the largest and most inclusive syntheses of research on effective professional development conducted to date. Scholars from the American Institutes for Research analyzed find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
324
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(391 citation statements)
references
References 7 publications
11
324
0
16
Order By: Relevance
“…Numerous studies in the social sciences indicate that at least this length of time is needed for complex multilevel interventions to influence desired outcomes (studies summarized in Fixsen, Naoom, Blasé, Friedman, & Wallace, 2005). However, other research indicates that less time is needed, suggesting that only 30 hours of PD may be needed to bring about instructional improvement (Guskey & Yoon, 2009). Given the demands on teachers' time in many schools around end-of-the-year accountability testing, effects for teachers who are new to a school may be maximized only if a coaching program is well established and engages teachers in intensive PD at the very beginning of the school year.…”
Section: Implications For Implementing Literacy-coaching Programsmentioning
confidence: 99%
“…Numerous studies in the social sciences indicate that at least this length of time is needed for complex multilevel interventions to influence desired outcomes (studies summarized in Fixsen, Naoom, Blasé, Friedman, & Wallace, 2005). However, other research indicates that less time is needed, suggesting that only 30 hours of PD may be needed to bring about instructional improvement (Guskey & Yoon, 2009). Given the demands on teachers' time in many schools around end-of-the-year accountability testing, effects for teachers who are new to a school may be maximized only if a coaching program is well established and engages teachers in intensive PD at the very beginning of the school year.…”
Section: Implications For Implementing Literacy-coaching Programsmentioning
confidence: 99%
“…Other research found that teachers were more likely to change their instructional practice when participating in PD programs that offered ongoing on-site support and teacher networks that could work collaboratively within and across schools and districts (Corcoran, McVay, and Riordan, 2003). This is consistent with a larger body of scholarly work suggesting that effective PD is sustained and intensive (Marrongelle, Sztajn, and Smith, 2013;Loveless, 2013) and involves collective participation and group work (Desimone, 2009;Elmore, 2002;Guskey and Yoon, 2009;Wei et al, 2009;Elliott et al, 2009).…”
Section: Administrator and Teacher Professional Developmentmentioning
confidence: 74%
“…Researchers have identified features of professional development that support the transfer of learning to classroom practice (Avalos, 2011;Darling-Hammond & Falk, 2013;Desimone, 2011;Guskey & Yoon, 2009;Timperley, 2008 While the impact on student achievement is a critical indicator of the effectiveness of professional development, we believe the impact of professional development on teacher knowledge and instructional practice is also relevant, as these are worthwhile outcomes in themselves that support increased learning for students. (p.15) Job-embedded learning is a key feature of professional development that supports teachers as adult learners.…”
Section: Professional Developmentmentioning
confidence: 99%